Warung Kaleng Kaleng / Fakrul Azzim Abdullah … [et al.] - Abdullah, Fakrul Azzim; Mohd Nazir, Nazrin Syazwani; Safar, Syazwanie; Mohd Rafie, Nur Izzatul Syahirah; Abd Gani, Nur Aina Shuhada (2021)
This assignment focuses on Malaysian small enterprises. Warung Kaleng Kaleng, a small business that sells food and beverages, was picked by our group. This small business is located in Kampung Penerok Kukup Pontian, Johor. This stall began operations during the first phase of the Movement Control Order (MCO), which is it was started in 26 Jun 2019. Warung Kaleng Kaleng is an ownership business and the founder is En Abdullah bin Mohamed. Encik Abdullah, the owner of Warung Kaleng Kaleng, opened the shop in front of his house because it is the major way into the community. This is Encik Abdullah's first business, and it was started by the owner, who is Encik Abdullah himself. Initially, the business was only a meal delivery service from home, but after the owner had enough funds, the owner wanted to create a stall called Warung Kaleng Kaleng. This is a family-run enterprise maintained by the En Abdullah family. Encik Abdullah is the cook for his stand, and his second son, Nazirul Amin bin Abdullah, assists him. Encik Abdullah and his son Nazirul Amin were the chef and chef assistant, respectively, in charge of preparing dishes and servicing customers. The business is open every night of the week and closes solely on Thursdays. Warung Kaleng Kaleng has offered a variety of cuisines to customers, with the most popular dishes being char kuey teow and tomyum. Aside from the delicious dishes that they made, they also offered a decent and inexpensive price for all of their dishes.